Innovaciones incrementales e innovaciones radicales: un estudio de las características intrínsecas de los equipos para el desarrollo de nuevos productos - López Sánchez, José Ignacio; Sandulli, Francesco D.; Rodríguez Duarte, Antonio; Minguela Rata, Beatriz (Cuadernos de Estudios Empresariales, 2006)
The present paper studies intrinsic characteristics of teams for new products development (characteristics of team members, characteristics of project leader, management support, autonomy degree, and multifunctional degree), as well as the difference in these characteristics between teams for incremental innovations and teams for breakthrough innovations. In order to do that, a sample of Electronic Components manufacturing firms in Spain was analyzed. We took the new product development project as analysis level.